Effect of various intracanal medicaments on the bond strength of self-adhesive resin cement to root canal dentin - Hakan Arslan; Hüseyin Sinan Topcuoglu; Gokhan Saygili; Oznur Tuncay; Yavuz Altintop (Taylor & Francis Group, 2015)
Objective: It has been shown that the irrigating solutions and medicament used during root canal treatment may affect the bonding strength. The aim of this study was to evaluate the effect of triple antibiotic paste (TAP), double antibiotic paste (DAP) and calcium hydroxide (CH) on the bond strength to root dentin of self-adhesive resin cement. Materials and methods: Forty-eight single-rooted human teeth were prepared and randomly divided into one control and three experimental groups (dressing with TAP, DAP or CH). After removal of intracanal dressing, post-spaces were created and fiber posts cemented to the root canal using a self-adhesive resin cement. A push-out test was performed. The data obtained from the push-out test were analyzed using analysis of variance and Bonferroni post hoc tests (p = 0.05). Results: TAP decreased the bond strength of self-adhesive resin cement bond strength to root dentin compared to the control group (p = 0.012), while CH and DAP did not influence this (p > 0.05). The majority of specimens exhibited adhesive failures. Conclusions: TAP decreased the bond strength of self-adhesive to the root dentin compared to the control group.